TutorBuddy : development of mobile-web based system for peer-to-peer personal tutoring services - Lim, Jorina (Nanyang Technological University, 2020)
In a university setting, it is common knowledge that students who already have seniors in the same course have a decided advantage. Other than getting to know about coursework and other relevant information beforehand, they also get to engage their seniors should they have any questions when revising for their final examinations. While a lot of professors do have walk-in consultation hours, some students might have other activities that do not allow them to fully utilise those. This project aims to level the playing field for students who might not be as well connected by having a platform where they can engage seniors who have done well in certain modules for help in their studies and coursework. This report serves to document the breakdown of the problem and detailed explanation of the platform’s technical implementation.